KEPENTINGAN INDONESIA MELAKUKAN EKSPOR TEH KE INGGRIS PADA TAHUN 2015-2017 - Silvi Pratiwi; Den Yealta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research aims to find out what Indonesia's interest to export tea to the United Kingdom in 2015-2017. This research also aims to determine the tea plantations in Indonesia and explain the value of Indonesian tea exports to the United Kingdom.The perspective used in this research is the Liberalism perspective, liberalism states that an interdependent world economy is based on free trade, specialization, and the division of international labor. This study uses a qualitative method in which both primary and secondary data are obtained from journals, books, theses, bulletins, press releases and relevant sites that explain the importance of Indonesia to export tea to the United Kingdom.The result of this research is that the high demand for world tea has become a great opportunity for Indonesia to be able to continue to develop tea exports and to dominate a larger market share. The increase in tea consumption is based on the world population growth that will increase above five percent but also coupled with the incessant promotion of tea about physical health carried out by tea producers around the world. Tea commodity has an important role in the national economy, namely as a source of farmer income, employment, State sources of foreign exchange, encouraging agro-industry regional development and environmental preservation. The economic and cultural fields are a way to strengthen bilateral relations between Indonesia and the United Kingdom. Keywords: Interests, Tea, Export.